2017
DOI: 10.21608/jrciet.2017.24458
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Corpus Approach in Developing EFL Writing Skills

Abstract: he aim of the present research was to investigate the impact of utilizing the corpus approach on developing EFL writing skills among student teachers. The participants of the study consisted of third year English section students enrolled in Faculty of Education, Benha University (N=23). The study followed the one-group pre-post test design. In addition, it was a mixed-research study including both quantitative and qualitative methods for collecting and analyzing the data in order to enhance the credibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is assumed that corpus output data, which contains examples of language sentences analyzed according to their contexts and keywords, are effective for L2 language learning, specifically academic writing and vocabulary acquisition (Khorsheed, 2018;Qoura, Hassan, & Mostafa, 2018). Numerous studies in the Second Language writing area like those of Abdel-Haq (2017), Al-Howishil (2019), Al-Qahtani (2021), Sun and Hu (2020), Vyatkina (2018), and Wu (2016) have found that corpus tools assisted academic writing processes to be more reliable (with large data) and more empirical (with real language data).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that corpus output data, which contains examples of language sentences analyzed according to their contexts and keywords, are effective for L2 language learning, specifically academic writing and vocabulary acquisition (Khorsheed, 2018;Qoura, Hassan, & Mostafa, 2018). Numerous studies in the Second Language writing area like those of Abdel-Haq (2017), Al-Howishil (2019), Al-Qahtani (2021), Sun and Hu (2020), Vyatkina (2018), and Wu (2016) have found that corpus tools assisted academic writing processes to be more reliable (with large data) and more empirical (with real language data).…”
Section: Introductionmentioning
confidence: 99%